TINGKAT KESEJAHTERAAN PETANI BERDASARKAN PENDAPATAN USAHA TANI TANAMAN SAWIT (Elaeis guineensis jack) DI DESA BENDANG RAYA KECAMATAN TENGGARONG - Aloysius Abel Dorage; Elisa Herawati; Fathiah Fathiah (JURNAL AGRIMENT, 2021)
The study is supported by the growing scale of land or land that is used for palm plants, both inindustrial sectors and in communities that strive to farm on private land, which is used to providesustainable income.The aim of the researchers is to know the welfare rates of farmers based on theincomes of the palm farm, the method used is proportionate random sampling to the number of 35people in the village bendang group and then analyze each of the respondents from gender, age andeducation, as well as to identify the farmers from the standpoint of jobs before attempting the palmfarm before attempting the palm farm, Income after the existence of the small farm, expenses for theliving and expenses left over from the revenues used for living expenses. As a result of the studyconducted, 28 people (80%) of farmers in the small and prosperous tilapia made enough profit tomeet their daily needsIncome ranges between $4,000,000-rp 10,000,000 and there are also 7 Thepeople (20%) who feel that they are not making ends meet in terms of the income from the non-oiltankers they are working on because some things such as unachievable harvests are affectingunusually low income. The result of research being done is level The welfare of palm plant farmers inthe village is a big sprout The southeast is in the welfare category judging by the income from thebusiness Just start the palm.